Towards a Dialogic Foundation for the Design of Educational Technology - Wegerif, Rupert; Major, Louis (The Theory of Educational Technology, 2023)
This chapter summarises our investigation into the theory of education technology and outlines a dialogic theory which we hope will prove useful as a foundation for educational technology design. To better understand education and how to improve it, we need to take technology seriously and listen to its ‘voice’. Our proposed dialogic theory focuses on how to design educational technology to support the opening, widening and deepening of dialogic spaces. It is about designing pedagogy with technology to facilitate the dynamic inter-weaving of educational dialogues at different spatio-temporal scales, linking short-term face-to-face dialogues to longer-term and more global dialogues.